The Role of EFL Teachers’ Emotioncy in Preventing Students’ Boredom and Pessimism - Xiaoshi Zhang (Frontiers in Psychology, 2022)
It is widely approved that emotions play a critical role in language education. This inspires EFL teachers to establish a classroom oriented toward students’ emotions and senses involved in the teaching/learning processes. Such an emotioncy-based pedagogy can bring about various positive outcomes in second/foreign language education. In tune with this, the present study briefly reviews the definitions, models, roots, and potentials of emotioncy in stopping student’ boredom and pessimism. Moreover, it makes some references to empirical inquiries in this line of research to strengthen its scientific basis. Finally, the study presents a number of implications for teachers, teacher educators, and researchers in language education urging them to focus on students’ emotions and senses more than before.